Determining the Temporal Change in Tuz Gölü between 2000-2020 by Remote Sensing - Nuriye Ebru Yıldız; Zeynep Çetiner (Turkish Journal of Agriculture: Food Science and Technology)
Changes in the landscape become extremely destructive and many heritage values and resources are irreversibly lost. The speed, frequency and magnitude of these changes in the landscape increased in the second half of the 20th century, especially with the impact of human activities. Remote sensing is the most widely used method for determining the change in the landscape. In the research, MNDWI, NDVI and NDMI techniques, which are frequently applied in remote sensing, were used in order to determine the landscape change in Salt Lake. Thus, the changes in the built area, water surface and land cover between the years 2000-2020 in Salt Lake were determined. According to the MNDWI and NDMI Analysis results, a decrease was observed in the water surface width and moisture content in Salt Lake between 2000 and 2020. In the steppe areas south of Salt Lake, the increase in tree cover due to the change in land use type was determined by NDVI analysis. Therefore, it is possible to say that there is an increase in the amount of moisture in these areas. In addition, it was determined that the increase in agricultural activities in the region caused a change in land use types and the amount of green space in the region changed at this rate. With the mentioned methods, negative changes in the landscape as a result of human activities on the landscape can be determined practically. Thus, it will be possible to predict the negative consequences of climate change and take precautions.